Potential Commercial Evaluation Of Kaolin Clay Deposit From Different Origin And Genesis - Aziz, Siti Nazalinda Abdul (Universiti Sains Malaysia, 2017)
Clay from Lenggong (LA 1), Tanjung Rambutan (TR 1) and Trong (TA 1), Perak with different origin and genesis were analysed to evaluate their potential commercial for industrial uses. Lenggong and Tanjung Rambutan clay is primary kaolin clay deposit whereas Trong clay is a secondary clay deposit. They were analysed by using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) with Energy Dispersive X-Ray (EDX), Differential Thermal Analysis (DTA) / Thermogravimetric Analysis (TGA) and X-ray Fluorescence (XRF) analysis. Other test included particle size analysis, moisture content, plasticity, color, firing test, pH test, and fired body test are also done. Kaolin from Lenggong and Tanjung Rambutan have silica content of 64.39% and 56.22%, iron content (Fe2O3) <1% and rutile content <1% meet the specifications of ceramic industry. Tanjung Rambutan kaolin also has potential to be commercialized as raw material for filler or coating material in paper or paint manufacturing. However, finer size particle should be used to improve its fired body properties. Shrinkage value for all clay in this project is significantly high which is > 11% but it is increasing with firing temperature from 700oC to 1100 oC. There are several properties of Trong clay that meet the specifications of industry but its iron content is quite high for the clay to be used in industry. One of the way to improve the quality of the clay is to reduce the amount of iron content in the clay by using organic acid leaching method.